Spanduk Penolakan Vaksin Covid-19: Kajian Semiotik Multimodal - Arini Prishandani; Nurainun Ainun; T. Thyrhaya Zein (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2021)
The purpose of this study was to see the meaning of the Covid-19 vaccine rejection advertisement or banner on social media on the @Indonesian_flatearth_society account. The method used in this research was qualitative method. The method to analyze using semiotic analysis of verbal and visual communication by Kress van Leeuwen. The analytical technique used in this research was reading image. The source of this research data was taken from the Covid-19 vaccine rejection campaign advertisement on Instagram social media "Indonesian_flatearth_sociaty". The data for this research were advertisement images or banners for the rejection of the Covid-19 vaccine on social media on the @Indonesian_flatearth_society account which was uploaded on December 10, 2020 and June 14, 2021. The results of the discussion of this study were semiotic multimodal studies that can be carried out using reading images technique. Each image have representational and interactive meaning that could be analyzed through Kress and van Leeuwen's 3 systems, namely information value, salience (bulge), and framing (frame). The analysis of the verbs found in each picture is that there are possessive sentences, persuasive sentences, and proverbs.